Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/chir.20738
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective plasma protein binding of amlodipine

Abstract: The binding of the (R)- and (S)-enantiomers of amlodipine to bovine serum albumin (BSA), human serum albumin (HSA), alpha(1)-acid glycoprotein (AGP), and human plasma (HP) was studied by equilibrium dialysis over the concentration range of 75-200 microM at a protein concentration of 150 microM. Unbound drug concentrations were determined by enantioselective capillary electrophoresis using 50 mM phosphate buffer, pH 2.5, containing 18 mM alpha-cyclodextrin as background electrolyte. Saturation of the protein bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…It has been recognized that preclinical data from animals cannot be extrapolated to humans 63 . Further studies also showed that stereoselective differences are dependent on species 28,29 . Nevertheless, mammalian results are occasionally consistent with human disposition 64 .…”
Section: Stereoselectivity Of Plasma Protein Binding To Chiral Drugsmentioning
confidence: 92%
See 2 more Smart Citations
“…It has been recognized that preclinical data from animals cannot be extrapolated to humans 63 . Further studies also showed that stereoselective differences are dependent on species 28,29 . Nevertheless, mammalian results are occasionally consistent with human disposition 64 .…”
Section: Stereoselectivity Of Plasma Protein Binding To Chiral Drugsmentioning
confidence: 92%
“…To illustrate enantioselective drug-protein binding, classical methods, such as equilibrium dialysis (ED), ultrafiltration (UF) and ultracentrifugation (UC), are commonly combined with chiral separation techniques 27,28,29 . ED is an apparatus with two compartments separated by a semipermeable membrane, and only unbound drug molecules can permeate through the membrane.…”
Section: Methods and Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the binding of drugs to plasma proteins can be stereoselective [11,12], the present study describes, for the first time, the analysis of unbound concentrations of the tramadol, M1 and M2 enantiomers in human plasma and the application of this method to pharmacokinetic studies on patients with neuropathic pain treated with a single dose of racemic tramadol. The method described is derived from a study recently published by our group in which total concentrations of the tramadol, M1 and M2 enantiomers were analyzed in rat plasma [13].…”
Section: Introductionmentioning
confidence: 99%
“…Binding of UK-390957 to human plasma proteins was determined by equilibrium dialysis. Human plasma protein binding values for propranolol (Rodgers and Rowland, 2007) and amlodipine (Maddi et al, 2010) were taken from the literature. BPR measurements for all three compounds were made using heparinized human blood (for further details, see Allan et al, 2008).…”
Section: Methodsmentioning
confidence: 99%